Frailty index and adverse outcomes in older patients in haemodialysis. (July 2022) - Soldati, Anna; Poggi, Marta Maria; Azzolino, Domenico; Vettoretti, Simone; Cesari, Matteo
Highlights: The high clinical complexity of older people makes them at greater risk of poor outcomes when undergoing haemodialysis. Frailty is a strong predictor of adverse outcomes in all stages of chronic kidney disease. This is the first study applying the frailty index model in a population of haemodialysis patients. Frail individuals present higher risk of hospitalizations and mortality. The frailty index may support the identification of those patients that may benefit the most from an adapted and personalized plan of care. Abstract: Background: : In older people, the prevalence frailty is inversely proportional to renal function, therefore it is supposed to be the highest in haemodialysis patients. However, frailty and its association with adverse outcomes have been scarcely investigated in this population. The aim of the present study was to characterize the frailty status and explore its association with hospitalization and mortality in a cohort of older patients undergoing chronic haemodialysis. Materials and methods: : This is a retrospective longitudinal study based on data from 105 older patients undergoing haemodialysis for at least 3 months. We computed a 24-item frailty index (FI) based on sociodemographic, clinical and biological data collected at baseline. During the follow-up, death and hospitalizations events were recorded. Unadjusted and adjusted Cox proportional hazard models were performed to test the association of frailty with hospitalization and death. Results: : Mean age of the patients was 79.1 (SD 7.6) years, and their mean FI was 0.23 (SD 0.10). About 55% of patients were classified as frail (i.e., FI≥ 0.25). Patients were observed for 21 (interquartile range [IQR] 8–32) months. Overall, during the follow-up, 75% of patients required hospitalization and 28% died. Frail subjects where at higher risk of hospitalization (HR 1.60, 95% CI 1.00–2.57, p  = 0.05) and of all-cause mortality (HR 2.52, 95% CI 1.10–5.80,   p  = 0.03) Conclusions: : Frailty is highly prevalent among older people undergoing haemodialysis. Frail individuals present a higher risk of hospitalizations and mortality. The FI is a reliable tool to study vulnerability in this population.